Review of Fatigue Assessment Approaches for Welded Marine Joints and Structures - Pasqualino Corigliano; Vincenzo Crupi (Metals, 2022)
Welded joints are widely used in many sectors and represent the main joining technique also in the marine industry. The welded joints are sites of high stress concentrations and are subject to severe conditions for the marine environment. The design of marine welded joints has to consider the effects from wave loads, ship motions and loading/unloading operations and corrosion effects. The aim of this scientific work is to discuss about the state of the art of the standards and the approaches for predicting the fatigue life of welded joints used for the marine industry. Several approaches are examined in order to provide an overview and highlight the advantages and limitations of each method. Furthermore, recent advances in welding of dissimilar metals and autonomous welding are considered.